MODEL SIR DENGAN ADANYA PENGARUH VAKSINASI DAN IMIGRAN - Noor Fakhriani; Yuni Yulida; Faisal Faisal (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2015)
Some major countries, immigration is a significant factor in the epidemic of a disease. Because the disease follows a predictable pattern of illness, so it can be checked with a standard SIR Model. Kermack and McKendrik SIR models can be developed with the effect of vaccinations and immigrants. The model is built on the assumption, and then determines the vaccination of reproduction number (Rv), determines the equilibrium point on the model, determines the type of stability of the equilibrium point and makes a simulation with the parameter values.